The Effect of Ethanol Extracted of Balsamina (Impatiens balsamina Linn) leaf on the Growth of Candida albicans In Vitro - Nadia Naitullah; Faisal Jamin; Frengki Frengki; Maryulia Dewi (Jurnal Medika Veterinaria, 2014)
This research aimed to determine the effect of ethanol extract of Impatiens balsamina Linn leaves on the growth of Candida albicans in vitro. One kilogram of Impatiens balsamina leaves which grows in Aceh was used. The leaves were washed, dried and blended into powder. The powder was then extracted with ethanol, filtrated, and evaporated. The crude extract was then made into serial concentration of 100, 75, 50, and 25%. The test of the effect of giving ethanol extract in Impatiens balsamina Linn is determined by the Kirby-Bauer disc diffusion method. Results showed that inhibition zones for 0, 25, 50, 75, and 100% were 0.0, 8.66±1.53, 11.66±1.55, 13.66±1.52, and 6±5.29 consecutively. It can be concluded that the ethanol extract of Impatiens balsamina Linn leaves± inhibit the growth of Candida albicans.Key words: Candida albicans, balsamina leaf, Impatiens balsamina Linn, extract